微分方程 $y^{\prime \prime}+2 y^{\prime}-3 y=\mathrm{e}^x$ 的通解为
$ \text{A.} $ $C_1 \mathrm{e}^{-3 x}+C_2 \mathrm{e}^x-\frac{1}{4} \mathrm{e}^x$. $ \text{B.} $ $C_1 \mathrm{e}^{-3 x}+C_2 \mathrm{e}^x-\frac{1}{4} x \mathrm{e}^x$. $ \text{C.} $ $C_1 \mathrm{e}^{-3 x}+C_2 \mathrm{e}^x+\frac{1}{4} \mathrm{e}^x$. $ \text{D.} $ $C_1 \mathrm{e}^{-3 x}+C_2 \mathrm{e}^x+\frac{1}{4} x \mathrm{e}^x$.
【答案】 D

【解析】 【解析】 $y^{\prime \prime}+2 y^{\prime}-3 y=0$ 的特征方程为 $r^2+2 r-3=0$, 解得 $r_1=-3, r_2=1$, 于是 $y^{\prime \prime}+2 y^{\prime}-3 y=0$ 的通解为 $y=C_1 \mathrm{e}^{-3 x}+C_2 \mathrm{e}^x$. 因 1 是一重特征根, 于是应设 $y^{\prime \prime}+2 y^{\prime}-3 y=\mathrm{e}^x$ 的特解为 $y^*=A x \mathrm{e}^x$, 则 $\left(y^*\right)^{\prime}=A(x+1) \mathrm{e}^x,\left(y^*\right)^{\prime \prime}=A(x+2) \mathrm{e}^x$, 代人原方程得 $A(x+2) \mathrm{e}^x+2 A(x+1) \mathrm{e}^x-3 A x \mathrm{e}^x=\mathrm{e}^x$, 解得 $A=\frac{1}{4}$, 则 $y^*=\frac{1}{4} x \mathrm{e}^x$. 所以为 $C_1 \mathrm{e}^{-3 x}+C_2 \mathrm{e}^x+\frac{1}{4} x \mathrm{e}^x$.
系统推荐